Islamic law in Malaysia: the challenges of implementation - Trakic, Adnan; Hanifah Haydar Ali Tajuddin (Springer Singapore Pte. Limited, 2021)
Intro -- Foreword -- Preface -- Contents -- Contributors -- Chapter 1: Challenges in the Implementation of Islamic Law in Malaysia -- Introduction -- Key Objectives and Research Approach -- Structure and Framework -- Conclusion -- References -- Chapter 2: British Administration of Malay Peninsula and Its Impact on the Status of Islamic Law -- Introduction -- Status of Islamic Law Before the Foreign Occupation of Malay Peninsula -- Status of Islamic Law After the Foreign Occupation of Malay Peninsula -- Conclusion -- References -- Chapter 3: The Status of Islam and Islamic Law in the Malaysian Federal Constitution -- Introduction -- Islam in the Federal Constitution -- Islamic Law in the Federal Consitution -- Conclusion -- References -- Chapter 4: Islamic Criminal Law -- Introduction -- Overview of the Implementation of Islamic Criminal Law -- Islamic Criminal Law in the Malay Sultanate -- British Colonisation and Independence of Malaysia -- The Islamic Criminal Jurisdiction -- Phase I - After Independence -- Phase II - After 1980 -- Current Practice -- Use of Islamic Criminal Law to Combat Moral Issues -- The Relevance of Punishing Islamic Criminal Offenders -- Alternative Punishments under Islamic Criminal Law -- Issuance of Bond of Good Behaviour -- Community Service Order (CSO) -- Power to Admonish -- Possible Rehabilitative Programs -- Contentious Issues in Implementing Islamic Criminal Law -- Conclusion -- References -- Chapter 5: Islamic Family Law -- Introduction -- Underage Marriage -- Application to Marry for Man or Woman Under the Age of 18 - The Case of Selangor -- Muslim Child Marriage Applications by State -- Maintenance -- Maintenance Rate -- Maintenance Order -- Responsibilities of Beneficiaries -- Enforcement and Execution of Maintenance Order -- Polygamy -- Dissolution of Marriage -- Arbitration by Hakam -- Conclusion.